6P'S MARKETING COMPOUND: BUILDING PROSPEROUS COOPERATIVES" - Oliveira, Rafael Alves; Pereira, Juliana (International Journal of Allied Research in Marketing and Management (IJARMM), 2023)
This study delves into the construction of knowledge within specific domains and its evolution into scientific status. Traditionally, objectivity and logical coherence, cultivated through empirical research and experimentation, were considered the primary sources of knowledge advancement. However, this perspective has been challenged by scholars like Chevalier & Loschak (1980) and Serva, Dias & Alperspetedt (2010) who emphasize that scientific knowledge transcends mirroring reality, evolving into a system that critically interprets it. This evolution can give rise to schools of thought, theories, and models, fundamentally enriching the epistemological landscape. This investigation centers on the Marketing field, a subset of Administration. The emergence of Marketing as a science was significantly influenced by distinct Schools of Marketing Thought, including Commodities, Functional, Interregional Trade Approach, Institutions, and more, each evolving sequentially due to historical shifts like World War II. The aftermath of the war prompted the U.S. government to collaborate with academia in developing marketing strategies to stimulate post-war demand, thereby catalyzing Marketing's scientific discourse. This study contemplates the intricate process of knowledge maturation within disciplines, ultimately culminating in their recognition as science. By examining the trajectory of Marketing's transformation, it underscores the multifaceted elements that contribute to the establishment of a scientific field, moving beyond conventional notions of empirical investigation.